TEACHER’S ADAPTATION IN USING ENGLISH TEXTBOOK IN THE SENIOR HIGH SCHOOL DURING THE COVID-19 PANDEMIC - Ermilaty Silya Runtukahu; Mister Gidion Maru; Olga Rorintulus (Universitas Negeri Manado, 2022)
This paper aims to examine the teachers’ adaptation of using English textbook in senior high school during the covid-19 pandemic. Particularly, to find out which adaptation strategies are most frequently implemented by the teachers in adapting English textbook and what constrains do the teachers encounter in adapting the textbook. Mix-Method designed was employed to the study. The data were taken from 11 teachers from 5 senior high schools in Sulawesi Utara province through questionnaire. The findings of the study revealed that simplifying was the most popular strategy utilized by the teachers. The process of adding was the second most popular as extending used 38 times ( 21%) and expanding used 37 times ( 20%). Subtracting and replacing were not commonly used as the strategy. Most of the teachers ( 81,82%) found some constrains in adapting English textbook. The major constrains related to the issues of the students’ need, background and their language proficiency, and the internet connection problem which affects the adapted material presentation and the time teaching allotment.